Modified Keystone Flap: A Versatile Reconstruction for Mastectomy Defects – Our Clinical Experience - Anastasia Dessy Harsono; Dominic Melino Tjokrovonco (Perkumpulan Kedokteran Militer, 2024)
Introduction: The closure of extensive defects in reconstructive surgery is a common challenge. The keystone flap technique has gained popularity due to its adaptability and reliance on fascia, providing a reliable blood supply and offering a better match for skin color compared to skin grafts. However, keystone flap necrosis can occur due to tension and inadequate tissue perfusion. To address this, a modified keystone flap technique called the